The Differential Impact of Uncertainty on Investment in Small and Large Businesses - Ghosal, Vivek; Loungani, Prakash (The Review of Economics and Statistics, 2000)
We study the impact of profit uncertainty on investment and whether or not this response is different in industries that are dominated by small firms versus those that are dominated by relatively larger firms. Our key findings are that the sign of the investment-uncertainty relationship is negative, and that the quantitative negative impact is substantially greater in industries dominated by small firms. These results are robust to accounting for potential endogeneity of the uncertainty measure, alternate procedures for measuring uncertainty, and alternate ways of segmenting industries into small- and large-firm groups.